HYPERSTHENE HORNFELSES OF THE KANDYGATAI COMPLEX, EASTERN KAZAKHSTAN - Sukhorukov V.P.; Plotnikov A.V. (My University, 2004)
The Kandygatai metamorphic block is situated within the Zharma strike-slip zone, which separates the Hercynides of the Zaisan and Caledonides of the Chingiz-Tarbagatai fold systems. Metapelites of the Kandygatai Complex have already been considered in the literature. Based on findings of hypersthenesillimanite, corundum-garnet, and hypersthene-clinopyroxene assemblages, this complex was attributed to the high-pressure granulites (T = 950-1000°C, P = 10-12 kbar and interpreted as an ancient sialic basement unique for this region. The present paper considers new petrological data, which make it possible to attribute this complex to the high-temperature-lowpressure rocks and propose a two-stage model of its formation.